Diffusion Coefficient Estimations by Thin-Channel Column Inverse Gas Chromatography : Preliminary Experiments - Mohd. Nawawi, Mohd. Ghazali (Universiti Putra Malaysia Press, 2000)
A thin-channel gas chromatography column was designed and used to measure diffusion coefficients of water and iso propanol in polymer phase via inverse gas chromatography (ICC) technique. The thin-channel column inverse gas chromatography technique proved to be a simple, fast and efficient alternative to sorption and desorption methods for measuring diffusion coefficients of permeants in thin polymer membranes films; the technique is especially useful when the problems associated with the irregularity of polymer distribution severely limit the accuracy of ICC measurement. Thin homogeneous chitosan membranes prepared by the solution casting technique were used as the stationary phase to provide a relatively uniform layer of polymer phase in the gas chromatography column. The diffusion coefficient of water was higher than that of isopropanol and diffusion coefficients of the permeants increased with column temperature. The effects of permeants size on diffusion coefficients were investigated on a series of alcohols: methanol, ethanol and isopropanol. The diffusion coefficients were inversely related to the permeants size.